Trends and Prospects of Bimetallic Exsolution. Issue 22 (24th February 2021) - Tang, Chenyang; Kousi, Kalliopi; Neagu, Dragos; Metcalfe, Ian S.
Abstract: Supported bimetallic nanoparticles used for various chemical transformations appear to be more appealing than their monometallic counterparts, because of their unique properties mainly originating from the synergistic effects between the two different metals. Exsolution, a relatively new preparation method for supported nanoparticles, has earned increasing attention for bimetallic systems in the past decade, not only due to the high stability of the resulting nanoparticles but also for the potential to control key particle properties (size, composition, structure, morphology, etc.). In this review, we summarize the trends and advances on exsolution of bimetallic systems and provide prospects for future studies in this field. Abstract : Exsolved bimetallic nanoparticles have attracted a lot of attention because they combine high stability and potential to control key particle properties (size, composition, structure, morphology, etc.) endowed by the exsolution method with additional unique properties mainly originating from the synergistic effects between the two different metals. These materials have enabled step‐change advances across a wide range of applications including electrochemical energy conversion and heterogenous catalysis. In this review the trends and advances of exsolution of bimetallic systems are presented and future directions of research provided.